Synthesis a Sol-Gel for Chemical Fiber Sensor - Bushra R. Mhdi; F. Hamode Jamal; Nahla A. Aljaber; Abeer H. Kalad (International Journal of Advances in Applied Sciences, 2013)
Sol–gel materials may found plenty of applications, e.g., as carriers for various substances, which can be exploited for sensing purposes or as drug releasing carriers. In this work, the fluorescence properties of two photosensitizers immobilized in silica based sol–gel materials were examined. Sol-gel derived silica possess many promising features, including room-temperature preparation procedure, porosity, chemical and physical stability. The material preparation procedure is described and practical remarks on silica-based sol-gels are included. It is reported that sol-gels with entrapped various molecules may be used in construction of implants and coatings with bioactive properties. It is shown how to exploit the sol-gel production route for construction of sol-gel coated fiber optic applicators for chemical sensor. We used a Sodium silicate(Na2 O3 Si) instead of the Trathyl Ortho Silicate (TEOS ) (Si (OC2 H5)4).We study the optical characteristics for this sample.